Development of decision support system (DSS) for forecasting of gray mold disease of castor (Ricinus communis L.) using internet of things (IOTs): Development of decision support system (DSS) for forecasting of gray mold disease of castor (Ricinus communis L.) using internet of things (IOTs) - R D PRASAD; C SARADA; B BALAJI NAIK; SANTOSH SAM KOSHY; R ARUTSELAN; P RAVIKUMAR; A VISHNUVARDHAN REDDY (Journal of Oilseeds Research, 2020)
Gray mold disease of castor caused by the fungus Botryotinia ricini is responsible for disease epidemics and heavy yield losses in castor growing regions of Telangana. An experiment was conducted in castor growing areas to understand the crop-weather-disease relations using wireless sensors, disease prediction models and Decision Support System (DSS). The DSS uses these weather data along with crop and management information to drive disease forecasting systems and a validated model of the disease to generate location specific management recommendations for fungicide application.